2021
DOI: 10.3390/s21175806
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of the Effects of Obstacle Negotiation and Turning on Gait Variability in Adults with Multiple Sclerosis

Abstract: Many falls in persons with multiple sclerosis (PwMS) occur during daily activities such as negotiating obstacles or changing direction. While increased gait variability is a robust biomarker of fall risk in PwMS, gait variability in more ecologically related tasks is unclear. Here, the effects of turning and negotiating an obstacle on gait variability in PwMS were investigated. PwMS and matched healthy controls were instrumented with inertial measurement units on the feet, lumbar, and torso. Subjects completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The reason for this change in gait is unknown, however, it can be speculated that shorter walking bouts may elicit more goal-direction actions towards activities other than walking while longer bouts are more purposeful [ 54 ]. Further expanding on the involuntary nature of shorter walking bouts, subjects may be more likely to be dual-task walking, in other words focused on more than just walking, and may be more impacted by the start-up and stopping strides [ 63 ]. This conjecture aligns with research on dual-task walking in PwMS that shows dual-task walking is more discriminative of impairment than single task walking [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this change in gait is unknown, however, it can be speculated that shorter walking bouts may elicit more goal-direction actions towards activities other than walking while longer bouts are more purposeful [ 54 ]. Further expanding on the involuntary nature of shorter walking bouts, subjects may be more likely to be dual-task walking, in other words focused on more than just walking, and may be more impacted by the start-up and stopping strides [ 63 ]. This conjecture aligns with research on dual-task walking in PwMS that shows dual-task walking is more discriminative of impairment than single task walking [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such indices include normalized velocity, stride length and hip range motion 67 . PwMS demonstrated a higher variability in their lumbar yaw range and lateral food deviation, particularly after turning and stepping over an object 68 . Similar to this finding, another study found more asymmetrical sway patterns when comparing PwMS with HC 69 .…”
Section: Imu and Motion Capturementioning
confidence: 97%
“…When conducting this extensive review, we found out that the vast majority of the studies used walking tasks to collect and analyse IMU and other motion-capture-based data [67][68][69][70][71][72][73] to assess gait and balance issues in PwMS. Overall, motion capture devices have revealed significant correlations between gait indices and subjective and objective walking abilities.…”
Section: Imu and Motion Capturementioning
confidence: 99%
“…One leverages temperature measurements to provide accurate differentiation between non-wear time, sleep time, and sedentary wake time [16]. The other demonstrates the importance of context in interpreting gait variability measures in persons with multiple sclerosis [17].…”
Section: Overview Of Special Issue On Applications Of Wearables In Di...mentioning
confidence: 99%